Humanising educational programme for the empowerment of women harmonious society in Afghanistan - Rahmani, Mohammad Saalem; Ahmad Dahlan, Abdul Rahman (Research Publish Journals, 2019)
Education is a challenge for most of people in Afghanistan especially for women who have been going through many ups and downs during past years. Women are experiencing many obstacles such as poverty, beliefs, culture, war and many more in order to be educated and their productive for the society. The year 2001 (pos era of Taliban regime) paved the way and opened a new chapter of education for most of people in Afghanistan especially women. Although, huge amount of money has been spent but still the result is not as expected. Currently, women are not playing an utilizable rule in terms of productivity for the society and most of them are burden on their husbands or parents. The purpose of this paper is to probe the bottlenecks and barriers that prevent educational empowerment of women in Afghanistan. This paper adapts the design & system thinking approach. The paper contribution is a conceptual and validated business model, in the form of BMC and VPCs, and as well conceptual humanising education programmes with digital platforms (digital teaching). The business model will help women to use their knowledge, skills, and value for innovative and national productivity towards sustaining society.